2020
DOI: 10.1080/03031853.2020.1742747
|View full text |Cite
|
Sign up to set email alerts
|

Gendered analysis of the demand for poultry feed in Kenya

Abstract: The objective of this paper was to estimate the demand for poultry feed among smallholder farmers in Kenya disaggregated by gender. Most poultry enterprises are owned and managed by women even in male headed households. The study utilizes cross-section data collected in July 2015 from a sample 386 poultry farmers randomly selected from three counties including Nakuru, Kisii and Kirinyaga Counties. The feed demand for poultry enterprise was analyzed by estimating a translog cost function and a system of cost sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(1 reference statement)
1
5
0
Order By: Relevance
“…The positive output price elasticities in this study was similar to the findings of who also reported positive coefficients for output supply in their respective studies (Williamson et al, 2004;Fabiosa et al, 2004;Praduman et al, 2010;Mailena et al, 2013;Macharia et al, 2020;Ashrit, 2021). The coefficient of price elasticity of spent layer in this study which was 1.12 was found to be higher than 0.27 obtained in the study (Maligaya and White, 1989).…”
Section: Elasticities For Own Price and Cross-price Of Poultry Egg Pr...supporting
confidence: 89%
See 2 more Smart Citations
“…The positive output price elasticities in this study was similar to the findings of who also reported positive coefficients for output supply in their respective studies (Williamson et al, 2004;Fabiosa et al, 2004;Praduman et al, 2010;Mailena et al, 2013;Macharia et al, 2020;Ashrit, 2021). The coefficient of price elasticity of spent layer in this study which was 1.12 was found to be higher than 0.27 obtained in the study (Maligaya and White, 1989).…”
Section: Elasticities For Own Price and Cross-price Of Poultry Egg Pr...supporting
confidence: 89%
“…According to Diewert, it is necessary to postulate a functional form for the cost or profit function in order to estimate input elasticities indirectly from those functions (Diewert, 1971). Following the formulation of the functional form, it is possible to differentiate it in terms of output and input prices to derive output and demand functions (Macharia, 2020). The features of the production function can be derived from either the cost or profit function when there is a one-to-one connection between the production and cost or profit functions (Pope, 1982).…”
Section: Econometric Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Chickens are important assets to both women and men; their roles include improving financial and food security and strengthening social relations, such as when given as gifts or slaughtered for visitors [ 4 ]. Women dominate small-scale chicken production [ 5 ], and they often control the sale of chickens and the proceeds [ 6 ]. These proceeds are a unique source of livelihood for women whose caretaking responsibilities can limit their income-generating opportunities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, poultry farming contributes to income, food security, and nutrition of many households, particularly in rural and peri-urban areas, and accounts for about 30% of the national agricultural GDP and about 7.8% of the total GDP (Kenya National Bureau of Statistics, 2014;Macharia et al, 2020). While important for livelihoods, .…”
Section: Introductionmentioning
confidence: 99%